The Importance of Learning Needs of CHF Patients from Patients\' and Nurses\' Perspective - F Rafii; Farangis Shahpoorian; Zahra Naasher; Mohsen Azarbaad; Fatemeh Hosseini (Iran University of Medical Sciences, 2009)
Background & Aim: Many of the leading causes of heart failure exacerbation can be prevented by teaching. However, as hospitalization continues to shorten nurses will be challenged to prioritize educational needs. A critical problem in attending to patient learning needs is identifying which learning needs are important to be learned. The nurse must be able to make educational decisions based on research findings and not simply personal experience. The aim of this study was to determine the perceived importance of learning needs of patients with heart failure compared with their needs identified needs by nurses.   Material & Method: This was a descriptive- comparative study in which 250 heart failure patients were recruited by convenience sampling. One hundred eighty one nurses were also selected by numerations in Tehran Cardiac Hospital of Shahid Rajaee. Data were collected by the "importance" component of CHFPLNI and were analyzed using SPSS- 11.   Results: The patients perceived the subscale of "Medication" and nurses perceived the subscale of "Risk Factors" as the most important titles to learn and were agreed upon the importance of "Diet Information". Subscales of "Activity", "Anatomy & Physiology" and "Psychological factors" were not so important to learn as perceived by both groups. The nurses perceived all of the 7 subscales and the total scale as having more importance for learning than the patients did (P=0.000). Female patients (P=0.007), patients with baccalaureate education (P=0.001) and nurses with advanced preparation (P=0.040) perceived the learning needs as more important than others.   Conclusion: Giving more importance to the learning needs of the patients by nurses and the difference of rating of the importance of learning needs by the two groups proposes the possibility of inattention to important learning needs from the patient perspective. The findings pave the nurses' way in prioritizing the learning needs of hospitalized heart failure patients.